Definitions of quality in higher education: A synthesis of the literature - Laura Schindler; Sarah Puls-Elvidge; Heather Welzant; Linda Crawford (Laureate Education Inc, 2015)
The aim of this paper is to provide a synthesis of the literature on defining quality in the context of higher education. During a search for relevant literature, the authors intentionally cast a wide net, beginning with a broad search in Google Scholar and followed by a narrower search in educational databases, including Academic Search Complete, Education Research Complete, Education Resources Information Center (ERIC), and SAGE Premier. The authors identified both peer-reviewed journal articles and publications from professional organizations, such as the International Organization for Standardization. The paper begins with a discussion of the existing challenges and strategies for defining quality. Next, the authors provide a conceptual model of quality based on their review of the literature. Then, they examine some considerations for defining quality assurance and provide recommendations to help bring greater clarity and alignment to existing quality assurance practices. Their findings reveal important gaps in the literature. First, more research is needed to determine the feasibility of developing a universal definition of quality that would apply to different types of institutions in diverse geographic locations. Second, more research is needed to better understand the influence of culture on the use and meaning of quality terminology. Specifically, research is needed to determine whether the terms, quality and quality assurance, are applicable across cultures and, if so, whether there are distinct regional and national meanings of these terms. Finally, the relationship between quality assurance and accreditation in the literature is unclear. DOI: 10.18870/hlrc.v5i3.244